What we call landscape - Maderuelo, Javier (Revista do Colóquio, 2023)
Based on a poem by the Korean Kim Sa-kat, the extension of the idea of landscape is explored, developed around the concepts of place, intertwining and “mysterious”. Article originally published as MADERUELO, Javier. What we call landscape. Visions, Universitat Politècnica de Catalunya – UPC, Barcelona, Spain, December 2003, no. 2, p. 20-25. Available at: <https://upcommons.upc.edu/handle/2099/10506>. Accessed on: November 23rd. 2023. Unless otherwise noted, content in this work is licensed under a Creative Commons: Attribution-NonCommercial-NoDerivs 3.0 Spain License